The role of regulatory T cells in immunity to malaria - Morter, RA (2019)
Immunity to malaria caused by Plasmodium falciparum is complex and poorly understood. Because of this, there remains no highly efficacious vaccine against disease. For the candidate malaria vaccines in the pipeline, immunogenicity has been observed to decline when tested in target populations in malaria-endemic countries, compared to malaria naïve volunteers in the UK. One potential explanation for this observation would be increased levels of immunoregulation caused by repeated malaria infections in endemic populations. Importantly, regulatory T cells (Tregs) are thought to expand during malaria infection, but the role they play in shaping the immune response and in determining disease outcomes remains unclear. It is also unknown whether malaria-expanded Tregs contribute to the suppression of responses to heterologous antigens such as vaccines. This thesis explores the role Tregs play in immunity to malaria using a controlled human malaria infection model in semi-immune Kenyan adults. It also investigates whether Treg activity is associated with the immunogenicity of an experimental pre-erythrocytic vaccine against malaria, ChAd63 / MVA ME-TRAP, in malaria-naïve adult populations and a malaria-exposed infant cohort in Burkina Faso. Cellular and cytokine responses are probed by ELISA, flow cytometry, antigen-specific in vitro assays and multiplex qPCR transcriptomics. The data presented identifies potential roles for Tregs in both natural and vaccine-induced immunity to malaria. Improving the immunogenicity and efficacy of malaria vaccines will require identifying reasons why current vaccines work sub-optimally in target populations, as well as greater knowledge of naturally protective immune responses to malaria, to inform the design of new vaccines. This thesis contributes data to both aspects of vaccine design.